Performance Analysis of Serial Concatenation Convolutional Codes Based on Amplitude Matrix - Mohammed Salih, Salih; Salim Sumait, Balasem (Anbar Journal of Engineering Sciences, 2009)
Serial Concatenation Convolutional Codes (SCCCs) encoder is built using a serial concatenation of two Recursive Systematic Convolutional (RSC) encoders, separated by an interleaver. These two RSC encoders depending on the trellis termination criteria are software implemented and the performance of each one of them is analyzed under different conditions and circumstances. The output data from the encoder are multiplied by an amplitude matrix (AM) at the transmitter side and the Inverse of Amplitude Matrix (IAM) at the receiver side. The reliability estimation, log-likelihood algebra, and soft channel outputs for Soft Output Viterbi Algorithm (SOVA) are examined. Then the modified Viterbi metric that incorporates a-priori information used for SOVA decoding is derived. A low memory implementation of the SOVA decoder is presented. The iterative SOVA for SCCCs is described with illustrative examples. The behavior of the SCCCs encoder-decoder scheme is tested under different circumstances with AM and without AM at the AWGN and Rayleigh fading channels with unlike frame sizes (FS) and constraint length (K). The results show that the performance of system with AM outperforms the other conventional system that worked without AM.